2018
DOI: 10.21149/9191
|View full text |Cite
|
Sign up to set email alerts
|

Validación del Cuestionario de Regulación Emocional Cognitiva en pacientes mexicanas con cáncer de mama

Abstract: [No disponible]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…9,10 In the face of stress events, patients with breast cancer may have a characteristic cognitive response, that is, cognitively they tend to catastrophize negative events, think that they should accept the events that occurred, and respond in a way that is nonadaptive. 11 Inappropriate cognitive regulation and nonadaptive coping strategies may cause individuals to be more prone to negative emotions, reduce QoL, affect patient compliance with treatment, and even increase disease progression. 12 Therefore, treatments that reduce stress and improve negative emotions (and, therefore, QoL) of patients with breast cancer and are essential to a supportive, patient-centered approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 In the face of stress events, patients with breast cancer may have a characteristic cognitive response, that is, cognitively they tend to catastrophize negative events, think that they should accept the events that occurred, and respond in a way that is nonadaptive. 11 Inappropriate cognitive regulation and nonadaptive coping strategies may cause individuals to be more prone to negative emotions, reduce QoL, affect patient compliance with treatment, and even increase disease progression. 12 Therefore, treatments that reduce stress and improve negative emotions (and, therefore, QoL) of patients with breast cancer and are essential to a supportive, patient-centered approach.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that the cognitive emotional adjustment strategies used by individuals in the face of stress events and negative emotions can affect their mental health 9,10. In the face of stress events, patients with breast cancer may have a characteristic cognitive response, that is, cognitively they tend to catastrophize negative events, think that they should accept the events that occurred, and respond in a way that is nonadaptive 11. Inappropriate cognitive regulation and nonadaptive coping strategies may cause individuals to be more prone to negative emotions, reduce QoL, affect patient compliance with treatment, and even increase disease progression 12.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, regarding the psychopathological representation of the construct, various investigations mention that difficulties in emotional regulation are associated with certain characteristic mechanisms in mental disorders ( C. Silva, 2005 ), such as anxiety and depression ( Mennin et al, 2007 ), additions ( McNally et al, 2003 ), eating behavior problems ( Pascual et al, 2011 ; Serppe et al, 2018 ; J. R. Silva, 2008 ), schizophrenic outbreaks ( Kring & Neale, 1996 ), personality disorders ( Glenn & Klonsky, 2009 ; Gratz & Roemer, 2008 ), among others. However, considering the measurement of the construct, significant relevance has been denoted on measurement questionnaires for emotional regulation ( Kinkead et al, 2011 ), ranging from a structured interview to self-applied scalar tests ( Caprara & Pastorelli, 1993 ; Gálvez-Hernández et al, 2019 ; Garnefski et al, 2001 ; Gratz & Roemer, 2004 ; Greenwald et al, 2003 ; Gross & John, 200 3; Hoshmand & Austin, 1987 ; Kamholz et al, 2006 ; Katz et al, 1999 ; Lane et al, 1990 ; Larsen & Prizmic, 2004; Rovira et al, 2012 ; Schutz et al, 2004 ; Stanton et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…R. Silva, 2008), schizophrenic outbreaks (Kring & Neale, 1996), personality disorders (Glenn & Klonsky, 2009;Gratz & Roemer, 2008), among others. However, considering the measurement of the construct, significant relevance has been denoted on measurement questionnaires for emotional regulation (Kinkead et al, 2011), ranging from a structured interview to self-applied scalar tests (Caprara & Pastorelli, 1993;Gálvez-Hernández et al, 2019;Garnefski et al, 2001;Gratz & Roemer, 2004;Greenwald et al, 2003;Gross & John, 2003;Hoshmand & Austin, 1987;Kamholz et al, 2006;Katz et al, 1999;Lane et al, 1990;Larsen & Prizmic, 2004;Rovira et al, 2012;Schutz et al, 2004;Stanton et al, 2000).…”
Section: Introductionmentioning
confidence: 99%